Liebig; the Master Chemist, - Kuslan, Louis I.; Stone, A. Harris (History of science series (Englewood Cliffs, N.J.), 1969)
A biography of the early nineteenth-century German chemist whose teaching and laboratory methods widely influenced the development of the science of chemistry.
Keywords: Juvenile literature; Liebig, Justus, Freiherr von, 1803-1873; dept.che; dept.nhstc; faculty_collection

Readings on Teaching Children Science - Kuslan, Louis I.; Stone, A. Harris (Wadsworth Pub. Co, 1969)
Keywords: Science; Study and teaching (Elementary); dept.che; dept.nhstc; faculty_collection

Teaching Children Science: An Inquiry Approach - Kuslan, Louis I.; Stone, A. Harris (Wadsworth Pub. Co, 1968)
Keywords: Science; Study and teaching (Elementary); Learning by discovery; dept.che; dept.nhstc; faculty_collection